Big Data and Shipping-managing vessel performance - Mandeep Virk; Vaishali Chauhan (Politeknik Negeri Padang, 2018)
Shipping business is staggering the trade by a substantial number which portrays the usage of leading technologies to deliver formative and reliable performance to deal with the increasing demand. Technologies like AIS, machine learning, and IoT are making a shift in shipping industry by introducing robots and more sensor equipped devices. The hitch big data originates as a technology which is proficient for assembling and transforming the colossal and divergent figures of data providing organizations with meaningful insights for better decision-making. The size of data is increasing at a higher rate because of the procreation of peripatitic gadgets and sensors attached. Big data is accustomed to delineate technologies and techniques which are used to store, manage, distribute and analyze huge data sheets with a high rate of data occurrence. This gigantic data is allowing to terminate the business by developing meaningful and valuable insights by processing the data. Hadoop is the fundamental basic for composing big data and furnishes with convenient judgments through analysis. It enables the processing of large sets of data by providing a higher degree of fault-tolerance. Parallelism is adapted to process big size of data in the efficient and inexpensive way. Contending massive bulk of data is a determined and vigorous assignment that needs an enormous crunching armature to guaranty affluent data processing and analysis.